THE FINANCIAL PERFORMANCE OF AGRICULTURAL HOLDINGS IN ROMANIA - REGIONAL ANALYSIS - BURJA, Camelia; BURJA, Vasile (Annales Universitatis Apulensis Series Oeconomica, 2015)
The paper presents an evaluation of the financial performance of agricultural holdings in Romania after the EU integration. To capture the most significant aspects of efficiency regarding agricultural activities, the paper presents a spatial perspective of performance on regions of development based on the evolution of some significant financial indicators. The financial ratios used in the paper present the evolution of performance for agricultural holdings by region, and by using the Data Envelopment Analysis method, a picture of their relative financial performance was obtained. The analysis revealed the top performing farms, the relative positioning of the others and their trends.